The Effects of Physical Activity and Obesity on Hypertension in Adolescents: Meta-Analysis - Maria Imakulata Berek; Agus Kristiyanto; Vitri Widyaningsih (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: The incidence of hypertension is always increasing every year both in Indonesia and in the world. Adolescents with high blood pressure are more likely to become adults with hypertension if not treated immediately. This study aimed to review the effects of physical activity and obesity on hypertension in adolescents using meta-analysis.Subjects and Method: Meta-analysis was performed by searching for articles from the database, namely Pubmed, Science Direct, Springer Link and Google Scholar. The keywords used are